Acceptance of Video Conference Technology as a Distance Learning Media with the TAM Method - S Sefrika; Enok Tuti Alawiah (IJISTECH (International Journal of Information System and Technology), 2020)
The covid19 pandemic has resulted in teaching and learning activities to be carried out online using video conferencing. This study aims to determine the acceptance of video conferencing technology in the teaching and learning process. The research method uses TAM (Technology Acceptance Model). TAM is a model used to measure the extent to which the level of user acceptance of technology, especially information technology. The results showed that the online learning system using video conferencing could be accepted by students as a solution for distance learning.